Gambaran Proses Asuhan Gizi Terstandar (PAGT) pada Pasien Diabetes Melitus Tipe II di Ruang Irna Paru - jannah, harisatul; Suhaema; Utama, Lalu Juntra; Sulendri, Ni Ketut Sri (Student Journal Nutrition (SJ Nutrition), 2023)
Background: Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia caused by deficiencies in insulin activity, secretion, or both. Nutritionists apply the Standardized Process of Nutritional Care (PAGT), a standardized procedure, to provide high-quality nutritional care services through a series of planned actions, such as evaluating nutritional needs and meeting those needs. By addressing the various elements that cause imbalances or changes in nutritional status, standardized nutritional care methods attempt to help patients overcome nutritional problems.  Research Objective: To determine the process of standardized nutritional care (PAGT) for diabetes mellitus patients in the pulmonary irna room at the Patut Patuh Patju Regional General Hospital (RSUD), West Lombok Regency.   Research Method: The methodology of this research is descriptive observational research using case studies taken from individuals suffering from type II diabetes mellitus.  Research Results: The patient on behalf of Mrs. 62 year old J was admitted to hospital with a diagnosis of Type II Diabetes Mellitus. From the results of the nutritional assessment, the patient's consumption level of energy, protein, fat and carbohydrates was in the low intake category. The results of anthropometric measurements of the patient had poor nutritional status. Based on laboratory results, the patient had laboratory examination levels that were in the abnormal category. The results of the patient's physical examination were in a weak condition with the patient's level of consciousness (CM) and clinical condition in the normal category. The nutritional diagnosis made was inadequate oral intake, decreased carbohydrate requirements, and poor adherence to the diet provided. The type of diet given is the 1500 kcal DM Diet. The results of monitoring and evaluation carried out for 3 days showed that the patient's food intake was still in the category of insufficient food intake (<80%), there was no improvement in nutritional status, the patient's laboratory progress fluctuated during the examination, and the results of the physical and clinical examination were normal and the results of the laboratory examination of blood sugar (GDS) decreased.  Conclusion: Based on the intervention carried out, it can be concluded that there was no increase in the patient's food intake, for anthropometric monitoring and evaluation the patient had a poor nutritional status (underweight), then monitoring and evaluating the patient's general condition improved, next, the results of monitoring and evaluating the patient's laboratory data not in the normal category.